Book review: Curbing catastrophe – natural hazards and risk reduction in the modern world - Szczuciński, Witold (Geologos, 2018)
Book review: Curbing catastrophe – natural hazards and risk reduction in the modern world, by Tim-othy H. Dixon, 2017. Cambridge University Press, Cambridge, UK. 300 pages. ISBN 978-1-107-03518-8.